Analisa Perilaku Pushover pada Pengujian Balok Beton Bertulang - Sudarno P Tampubolon (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
Beams are part of the building structure that is important to consider when designing the structure. Some failures that occur in beams due to beam reinforcement are not installed such as planning/ design procedures, this problem can cause structural failure. Knowing the behavior of the beam structure due to the given load can help predict the strength of the structural beam and the comfort of the planned structure. To determine and predict the strength and comfort of the reinforced concrete beam structure due to the received load, experimental and simulation tests are carried out. VecTor2 simulation is used to predict shear, crack, and displacement forces in reinforced concrete beams when displacement loads are applied. The bond stress-slip effect (0.139) has a good effect on the strength and hysterical response of reinforced concrete beams. From the results of pushover testing and simulations, it is obtained that the ratio for load capacity ranges from 1.00-1.095. In addition, the installation of 135˚ hooks on stirrups shows that the crack behavior that occurs forms an angle of 45˚, this indicates that the bond between concrete and reinforcement is going well, this can be seen from the analogous behavior principle of reinforced concrete beams.